Keefektifan Model Pembelajaran Kooperatif Tipe Tea Party dalam Keterampilan Berbicara Bahasa Jerman - Riskayanti Riskayanti; Wahyu Kurniati Asri (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2019)
The purpose of this study was to obtain data about the effectiveness of the Tea Party cooperative model in German speaking skills. This research is a quasi-experimental study. Data collection tecnique is speaking skills tests. Data were analyzed using t-test analysis. The results of data analysis show that t count 6.141> t table 1.998 at a significant level of 0.05. The results showed that the Cooperative Tea Party Type learning model was effectively used in  increasing students' German speaking skills